The Effect of Religiosity on Organizational Commitment through Work Values - EKİZLER, HÜSEYİN (My University, 2020)
Multitudinous studies conducted on organizational commitment and work values have emphasized a great significance of these concepts. In recent years considerable attention has also been accentuated on religiosity and its influence. The purpose of this study is to examine the impact of religiosity on organizational commitment through work values. Organizational commitment scale developed by Meyer and Allen (1991), religiosity scale developed by Hoge (1972) and work values scale developed by Elizur (1996) wasused for measuring the variables. Data were collected by using convenience sampling technique through questionnaires from 261 participants employed in various companies located in Istanbul, Turkey. Results indicate that both intrinsic and extrinsic religiosity has a positive effect on work values. Also, these two dimensions of religiosity have a positive direct effect on continuance commitment, whereas normative commitment is positively affected by only intrinsic religiosity. Work values is found to be mediator of the relationship between extrinsic religiosity and continuance commitment. The findings extend current theories of the role of religion in working environment by examining the possible influence on work values.